The Relationship of Risperidone Therapy Pattern to The Symptoms That Appear in Schizophrenia Patients Under Out Patient Treatment - Aghnia Fuadatul Inayah; Putri Ardana Wahyu Andika; Alvina Arum Puspitasari (Green Publisher Indonesia, 2025)
Schizophrenia has a high psychosocial burden and environmental influences cause an increase in patient mortality. Management of schizophrenia can be done using two methods, namely pharmacological therapy and non-pharmacological therapy. Positive symptoms can be controlled with pharmacological therapy using antipsychotic medication. After treatment of positive symptoms, negative symptoms are likely to persist. Antipsychotics are the primary therapy for schizophrenia sufferers. Risperidone is known to be the first line for schizophrenia sufferers because of the mild reactions it causes.The therapy received by schizophrenia patients, either monotherapy or in combination, has an effect on the symptoms that appear in the patient. This study aims to evaluate the pattern of antipsychotic therapy given in relation to the symptoms that appear after being given therapy. It is known that at the Jombang Regional Hospital Mental Health Polytechnic there are patients with various mental disorders and most of them are schizophrenic sufferers with a low level of public awareness so they do not know the symptoms they are experiencing. The inclusion criteria in this study were patients diagnosed with schizophrenia who received the antipsychotic risperidone alone or in combination with other antipsychotics in the period January-December 2021. Data analysis used the Chi-square test to see the relationship between the administration of risperidone therapy patterns and the symptoms that appeared in patients. After the analysis was carried out, the results showed that the risperidone therapy pattern had no relationship with the symptoms that appeared after therapy. This can be caused by several factors including individual factors.